2008
DOI: 10.1088/1126-6708/2008/09/002
|View full text |Cite
|
Sign up to set email alerts
|

𝒩 = 5, 6 superconformal Chern-Simons theories and M2-branes on orbifolds

Abstract: Abstract:We explore further our recent generalization of the N = 4 superconformal Chern-Simons theories of Gaiotto and Witten. We find and construct explicitly theories of enhanced N = 5 or 6 supersymmetry, especially N = 5, Sp(2M ) × O(N ) and N = 6, Sp(2M ) × O(2) theories. The U (M ) × U (N ) theory coincides with the N = 6 theory of Aharony, Bergman, Jafferis and Maldacena (ABJM). We argue that the N = 5 theory with Sp(2N ) × O(2N ) gauge group can be understood as an orientifolding of the ABJM model with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
468
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(485 citation statements)
references
References 72 publications
16
468
0
1
Order By: Relevance
“…From the AdS/CFT correspondence, it was conjectured [1] from the gravity side that the free energy of M2-branes, the degrees of freedom of fundamental excitations in M-theory, is N 3/2 in the large N limit. After the proposal [2][3][4] that the N = 6 superconformal Chern-Simons theory with gauge group U(N 1 ) k ×U(N 2 ) −k and two pairs of bifundamental matters describes min(N 1 , N 2 ) M2-branes and |N 2 − N 1 | fractional M2-branes on the target geometry C 4 /Z k , this conjecture was confirmed from the gauge theory side. Namely, after using the localization technique [5], the partition function of the ABJM theory on S 3 , which is originally defined by the infinite-dimensional path integral, is reduced to a finite-dimensional matrix integration.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…From the AdS/CFT correspondence, it was conjectured [1] from the gravity side that the free energy of M2-branes, the degrees of freedom of fundamental excitations in M-theory, is N 3/2 in the large N limit. After the proposal [2][3][4] that the N = 6 superconformal Chern-Simons theory with gauge group U(N 1 ) k ×U(N 2 ) −k and two pairs of bifundamental matters describes min(N 1 , N 2 ) M2-branes and |N 2 − N 1 | fractional M2-branes on the target geometry C 4 /Z k , this conjecture was confirmed from the gauge theory side. Namely, after using the localization technique [5], the partition function of the ABJM theory on S 3 , which is originally defined by the infinite-dimensional path integral, is reduced to a finite-dimensional matrix integration.…”
Section: Introductionmentioning
confidence: 93%
“…Since the match of the Gopakumar-Vafa invariants is highly non-trivial, we are strongly confident of the relation with the local D 5 del Pezzo geometry. Although originally we adopt the ansatz (2.43) to determine the BPS indices to reduce the 3 Here and in the following, the norm |d| stands for the sum of all components of d = (d1, d2, · · · ), |d| = i di, and the summation |d|=d stands for that under this constraint…”
Section: Instanton Effectsmentioning
confidence: 99%
“…Subsequent work [4][5][6] revealed that such CSm theories, which can be generalized to SU(N )×SU(M ) [7,8], are equivalent to theories constructed using three-algebras whose structure constants enjoy lesser symmetry compared with that of the BLG theory.…”
Section: Jhep11(2013)050mentioning
confidence: 99%
“…One interesting feature of the ABJM theory is that it allows supersymmetry preserving mass deformation [17,18]. That is, the resulting mass-deformed theory called the mABJM theory has still N = 6 supersymmetry though the conformal symmetry of the original theory is broken under the deformation.…”
Section: Vacua Of the Mabjm Theory And The Llm Geometriesmentioning
confidence: 99%
“…Our analysis is based on the 3-dimensional mass-deformed Aharony-Bergman-Jafferis-Maldacena theory (mABJM) of massive M2-branes, which has N = 6 supersymmetry and U k (N )×U −k (N ) gauge symmetry, where k is the Chern-Simons level [17,18]. The mass-deformed theory is obtained from the original ABJM theory [19] by adding a relevant deformation which preserves the full supersymmetry as well as the JHEP04 (2017)104 gauge symmetry while the conformal symmetry is completely broken and the SU(4) global symmetry is reduced to SU(2)×SU(2)×U (1).…”
Section: Jhep04(2017)104 1 Introductionmentioning
confidence: 99%